Reconocimiento y medición del activo biológico de la compañía Agricola Bananatropical S.A. - Toca Pineda, Nancy del Rocio (My University, 2021)
International Financial Reporting Standards (IFRS) establish common rules for financial statements to be consistent, transparent and comparable around the world. These standards are issued by the International Accounting Standards Board (IASB), where it is specified how companies must maintain and report their accounts, defining types of transactions and other events that have financial impact. They were established with the purpose of creating a common accounting language so that companies and their financial statements can be consistent and reliable from one company to another and from one country to another. With regard to the development of this study, the purpose of this study is to analyze IAS 41 Biological Assets, to properly determine its measurement, valuation and accounting treatment in Compañía Agrícola BANANATROPICAL SA, it was analyzed in compliance with current accounting and tax regulations using a research approach and obtaining numerical and textual data in which they allowed a better solution of the problems that the company is going through. The study has a descriptive-explanatory scope since it led to the characterization of the study variables in which the biological asset must be valued reliably and reasonably. Biological Assets are important assets when carrying out economic activity, because this is the axis for carrying out the various processes and procedures to obtain economic benefits at the end of the fiscal year. By applying IAS 41 related to the Biological Asset to be able to carry out the Recognition and measurement of the Biological Asset of Compañía Agrícola BANANATROPICAL S.A., and thus improve the presentation of financial information.
Las Normas Internacionales de Información Financiera (NIIF) establecen las reglas comunes para que los estados financieros puedan ser coherentes, transparentes y comparables en todo el mundo. Estas normas son emitidas por el Consejo de Normas Internacionales de Contabilidad (IASB), donde queda especificado como las empresas deben mantener y reportar sus cuentas, definiendo tipos de transacciones y otros eventos que tienen impacto financiero. Fueron establecidas con el propósito de crear un lenguaje contable común para que las empresas y sus estados financieros puedan ser consistentes y confiables de una compañía a otra y de un país a otro. Con respecto al desarrollo del presente estudio tiene por objeto Analizar la NIC 41 Activo Biológico, para determinar adecuadamente su medición, valorización y el tratamiento contable en la Compañía Agrícola BANANATROPICAL S.A., fue analizado cumpliendo con la normativa contable y tributaria vigente utilizando un enfoque de investigación y obteniendo datos numéricos y textuales en el cual los mismos permitieron una mejor solución de la problemática que atraviesa la compañía. El estudio tiene un alcance descriptivo- explicativo ya que llevo a la caracterización de las variables de estudio en la cual el activo biológico debe valorarse de manera fiable y razonable. Los Activos biológicos son activos importantes a la hora de realizar la actividad económica, debido que este es el eje para la realización de los diversos procesos y procedimientos para obtener beneficios económicos al finalizar el año fiscal. Al aplicar la NIC 41 relacionado al Activo biológico para poder realizar el Reconocimiento y medición del Activo biológico de la Compañía Agrícola BANANATROPICAL S.A., y así mejorar la presentación de información financiera.
Keywords: NIIF; NIC 41; EMPRESAS BANANERAS; ACTIVO BIOLÓGICO